2010
DOI: 10.1094/phyto-100-9-0959
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Models for Germination and Infection of Pseudoperonospora cubensis in Response to Temperature and Duration of Leaf Wetness

Abstract: The influence of temperature and leaf wetness duration on germination of sporangia and infection of cantaloupe leaves by Pseudoperonospora cubensis was examined in three independent controlled-environment experiments by inoculating plants with a spore suspension and exposing them to a range of leaf wetness durations (2 to 24 h) at six fixed temperatures (5 to 30 degrees C). Germination of sporangia was assessed at the end of each wetness period and infection was evaluated from assessments of disease severity 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Of course, the methods described here provide only a description of the generalized epidemic wave-front and magnitude but provide no information about the disease risk of individual sentinel plots or counties. Disease risk at these scales requires more detailed information on precise weather conditions at the scale of crop canopy and long-distance transport and deposition of inoculum from mechanistic models (Arauz et al, 2010; Neufeld, Isard & Ojiambo, 2013; Ojiambo & Holmes, 2011). Nonetheless, the findings here suggest that the magnitude of epidemics at the landscape level may be largely determined by antecedents associated with overwintering success of the pathogen in southern latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, the methods described here provide only a description of the generalized epidemic wave-front and magnitude but provide no information about the disease risk of individual sentinel plots or counties. Disease risk at these scales requires more detailed information on precise weather conditions at the scale of crop canopy and long-distance transport and deposition of inoculum from mechanistic models (Arauz et al, 2010; Neufeld, Isard & Ojiambo, 2013; Ojiambo & Holmes, 2011). Nonetheless, the findings here suggest that the magnitude of epidemics at the landscape level may be largely determined by antecedents associated with overwintering success of the pathogen in southern latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Das and Bhattacharya (2006) found that electro magnetic field (EMF) strength of 0.88 T for 80 min has maximum stimulating effect on germination of gram seeds (Cicar arietium) and it may be assumed that under this condition the three-cell water potential forces act in the same direction on germinated seeds. Many authors (Arauz et al, 2010;Dias, 2001;Miller et al, 2003) have used some statistical functions for cumulative germination like Weibull function y = M(1-exp (-k(t-z) (-k(t-z))) (1/(1-c)) , Mitscherlich function y = M(1-exp (-k(t-z))), Gompertz function y = M(exp (-exp(-kt + b))) and logistic functions y = M/(1 + exp(-kt + b)). In these functions, y is cumulative germination at time t and M, k, z, b and c are empirically derived constants.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative models show that the effect of temperature on germination and infection is unimodal, with optimums of 15 to 17 • C and 20 to 22 • C, respectively (3), and the two variables increase in a sigmoidal fashion with increasing leaf wetness duration. These interactive effects have been described by a Weibull model, and in the presence of moisture temperature determines the rate and extent of infection by P. cubensis (3,71). The interactive effects are also dependent on the cucurbit host, with the effect being characterized mainly by the level of host susceptibility to P. cubensis (71).…”
Section: Models For Infection and Sporulation Of Pseudoperonospora Cumentioning
confidence: 99%